Management and cost accounting - Horngren, Charles T. (Harlow, England ; New York : Financial Times/Prentice Hall, 2005)
This text covers all the principle areas of management and cost accounting, underpinned by a strong European focus. Drawing on the latest research, surveys and case studies, new innovations and developments are also explored. Important concepts are brought to life through extensive application of techniques to real business situations.
Includes bibliographical references and index.
oif 13/03/15
Loan
Keywords: Cost accounting; Managerial accounting